2023
DOI: 10.1002/jia2.26061
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐based versus universal PrEP delivery during pregnancy: a cluster randomized trial in Western Kenya from 2018 to 2019

Abstract: Introduction Integrating pre‐exposure prophylaxis (PrEP) delivery for pregnant and postpartum women within maternal and child health (MCH) clinics is feasible and acceptable. It is unknown whether a risk‐guided model would facilitate appropriate PrEP use among MCH attendees better than universally offering PrEP. Methods The PrEP Implementation for Mothers in Antenatal Care (PrIMA) study was a cluster randomized trial to assess two models for PrEP delivery among pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This specific willingness to take PrEP by those with a perceived high risk may support the need to improve access to PrEP to all persons. A cluster randomized trial in Kenya reported no difference in PrEP uptake and HIV incidence between risk-based and universal PrEP delivery strategies in pregnant women [ 21 ]. The universal approach was reported to be less time-consuming and did not expose clients to uncomfortable discussions, hence being simpler [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This specific willingness to take PrEP by those with a perceived high risk may support the need to improve access to PrEP to all persons. A cluster randomized trial in Kenya reported no difference in PrEP uptake and HIV incidence between risk-based and universal PrEP delivery strategies in pregnant women [ 21 ]. The universal approach was reported to be less time-consuming and did not expose clients to uncomfortable discussions, hence being simpler [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in PrIYA uptake was 22% among pregnant and postpartum women and other AGYW ( 15 , 16 ). In the PrIMA trial, which also involved additional staff support, PrEP acceptance was 18.6% among pregnant and postpartum women ( 29 ). In contrast, PrEP uptake was substantially lower in the PrEPARE implementation science study focused on MCH, which did not provide additional staff, at 3.9% among those offered PrEP ( 30 ) ( Sila & Wagner, under revision ).…”
Section: Discussionmentioning
confidence: 99%
“…One study utilized standardized patient actors to address lack of effective provider training and found that the training was associated with significantly improved counseling quality ( 34 ). The PrIMA study tested risk-guided versus universal offer of PrEP to assess whether a simplified PrEP offer was sufficient within routine practice to alleviate the time burden of PrEP-specific risk screening; this trial concluded that universal offer is superior to risk-guided offer due to its simplicity and comparable performance ( 29 ). Point-of-care sexually transmitted infection testing was assessed to address the barrier of low risk perception; this pilot found that PrEP uptake was significantly higher among women who accepted point-of-care sexually transmitted infection testing ( 35 ) and point-of-care testing was highly acceptable ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…PrIMA description : Finally, PrIMA was a research study that provided additional staff to assist in study activities. The 20 public clinic sites involved in PrIMA were assigned to one of two arms in a cluster randomized trial; pregnant women seeking routine MCH care at these clinics either (a) self-selected into PrEP after receipt of PrEP counseling (Universal arm), or (b) were evaluated for HIV risk via an objective risk-scoring tool and offered HIV self-tests for at-home partner testing (Targeted arm) ( 32 , 33 ). In the Targeted arm, only individuals determined to be high risk for HIV acquisition were offered PrEP.…”
Section: Methodsmentioning
confidence: 99%